Studi Naratif Biografis: Gambaran Dukungan Keluarga dalam Perjalanan Usaha Wirausahawan Muda - Mutiara Rahma Eldita; Yanladila Yeltas Putra (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Many young people in Indonesia have a strong interest in starting their own businesses; however, only a small portion are able to turn this interest into a sustainable entrepreneurial career. This study aims to explore in depth how family support plays a role in the journey of young entrepreneurs, from the early stages of entrepreneurial exposure to the formation of entrepreneurial identity and personal values. The research employs a qualitative method with a narrative-biographical approach. Participants were selected using purposive sampling, and data were collected through semi-structured interviews with the main subject and significant others who have close relationships with the subject. The data were analyzed using Braun and Clarke’s thematic analysis technique, which focuses on identifying meaning and patterns within the subject’s life experiences. The findings reveal four main themes: (1) the process of early entrepreneurial learning and exposure, (2) the role and dynamics of family support in fostering entrepreneurial resilience, (3) turning points in career transformation and the formation of entrepreneurial identity, and (4) personal principles and values that guide business practices. The results emphasize that family support is not only material but also serves as a psychological and emotional factor that plays a crucial role in the success of young entrepreneurs in building and sustaining their businesses.